Analisis Pengawasan Pemerintah terhadap Peredaran Gelap dan Penyalahgunaan Narkotika di Kabupaten Sidrap - Nurul Mawahda; Abd. Firman Bunta; Vanya Dyah Pitaloka M.A.C.R; Sabrina Nadia (Ideas Publishing, 2025)
This study aims to provide an overview of the supervisory mechanisms applied in the investigation of illicit narcotics trafficking and abuse conducted by the Narcotics Investigation Unit of the Sidrap Resort Police, as well as the oversight of the implementation of narcotics-abuse prevention facilitation carried out by the local government, particularly the National and Political Unity Agency of Sidrap Regency. The research employed a qualitative approach to describe the procedures used for data collection, with data obtained through interviews, observations, and archival documentation.The findings indicate that governmental oversight of narcotics-related investigations conducted by the Narcotics Investigation Unit of the Sidrap Resort Police faces several challenges, especially during arrest operations. These challenges include the disruption of information networks following the apprehension of previous perpetrators and difficulties in securing physical evidence. Oversight by the local government in implementing narcotics-abuse prevention facilitation—performed by the National and Political Unity Agency of Sidrap Regency—remains limited to a few activities, such as enhancing community participation in narcotics-abuse prevention through public awareness programs, which have not been carried out optimally, and establishing cooperation with certain entities such as non-governmental organizations and law-enforcement institutions. Several responsibilities, however, have not yet been fulfilled, including drafting regional regulations on narcotics, involving FKUB, FKDM, and Kominda in narcotics-abuse prevention efforts, and formulating comprehensive programs and activities targeting narcotics-abuse prevention.